Analisis Pengendalian Persediaan Obat Kategori Av Dengan Metode Abc, Ven Dan Eoq Di Instalasi Farmasi Rumah Sakit Aura Syifa Kediri - Chandra Arifin; Tri Wijayanti; Gunawan Pamudji Widodo (Jurnal Farmasi Indonesia, 2023)
ABSTRACT Inventory Control Analysis Of AVMedicine CategoriesbyABC, VEN and EOQ Method In Pharmacy Installation at Aura Syifa Hospital Kediri.Pharmaceutical logistics management and pharmaceutical services aim to identify, prevent and resolve drug-related problems. Broadness of services and Aura Syifa Hospital Kediri participation in Jaminan Kesehatan Nasional (JKN) requires an efficient pharmaceutical supplies management. Regulations changes in Badan Penyelenggara Jaminan Sosial (BPJS) regarding tiered referral also change the pattern of drug consumption. In addition, arrears of BPJS patient claim payment at Aura Syifa Hospital Kediri during the last few months caused hospital to be slightly constrained in terms of operations and services, especially related to the procurement of medicines. Purpose of this study was to analyze control system and improve the efficiency of managing AV classification medicine using ABC, VEN and EOQ methods inpharmacy installation at Aura Syifa Hospital Kediri.This study wasdescriptive with retrospective data collected, data used in the period January 2018 - December 2018. Medicine analyzed were oral drugs, injections and infusions that were included in group A from the results of ABC analysis, group V from the results of VEN analysis so it was obtained BPJS medicine AV categories. Result of this study were combination of ABC and VEN analysis methods could identify drugs that require strict inventory control and prioritize 12 BPJS medicine in AV category. Pharmacy installation at Aura Syifa Hospital Kediri in 2018 did not meet cost efficiency that is: procurement frequency was higher than the EOQ method. Calculation of ABC, VEN and EOQ methods may improve efficiency in controlling AV classification medicine supplies in BPJS patients at IFRS Aura Syifa Kediri.